Photosensitive Hydrogel Creates Favorable Biologic Niches to Promote Spinal Cord Injury Repair. Issue 13 (9th May 2019) - Cai, Zhengwei; Gan, Yibo; Bao, Chunyan; Wu, Wanjiang; Wang, Xuebin; Zhang, Zetong; Zhou, Qiang; Lin, Qiuning; Yang, Yi; Zhu, Linyong
Abstract: Photochemistry is considered to be a promising strategy for hydrogels to mimic the complex and dynamic properties of natural extracellular matrix. However, it is seldom applied in 3D tissue engineering and regenerative medicine due to the attenuation of light. In this study, phenyl azide photchemistry and optical fiber technology are first used to localize adhesive protein on the inner surface of the nerve guidance conduit in a 3D hydrogel scaffold. In vitro coculture assay of neural stem cells (NSCs) shows that photoimmobilization of collagen significantly improves the adhesion and survival of NSCs in the conduit, and exhibits synergistic effect with the sustainable release of growth factor. After implantation in transected spinal cord, the optimized hydrogel scaffold is found to improve the locomotion recovery of rats 12 weeks after spinal cord injury (SCI). Histological analysis suggests that the designed hydrogel scaffold provides a favorable biological niche for neuronal regeneration, thus producing directional neuron tissue and promoting the repair of SCI. This study demonstrates a promising hydrogel scaffold for SCI repair and provides the first understanding of the photoimmobilization of adhesive protein in a 3D hydrogel conduit concerning its functions on spinal cord tissue restoration. Abstract : Through a photolithography technology, a conduit‐contained hydrogel scaffold is constructed and applied for spinal cord injury (SCI) repair in rats. Photoimmobilization of collagen in the conduit and sustained release of growth factor are proven to provide a favorable 3D microenvironment for improving neuronal regeneration, thus promoting locomotion recovery in severely transected SCI rats.